Fuzzy Based Chaotic Synchronization of Chen Systems - Bulut, Gulden Gunay; Guler, Hasan (Ieee, 2019)
Chaotic systems are used in many applications like secure communication, internet banking, image processing and transmission etc. because of their ease of modelling and their ability to be performed with inexpensive autonomous circuits. In all these applications, chaotic synchronization and chaotic control are needed to effectively work when performing with multiple chaotic systems. This study presents master-slave satellite synchronization of Chen chaotic system with fuzzy logic controller. Master-slave Chen systems were modelled in the LabVIEW environment and the simulation was performed for 30 seconds. At the 14th second, the fuzzy logic controller was activated and it is observed that the slave system followed the master system successfully.
1st Global Power, Energy and Communication Conference (IEEE GPECOM) -- JUN 12-15, 2019 -- Nevsehir, TURKEY
Keywords: synchronization; chen chaotic system; fuzzy logic controller; simulation; labVIEW